2018
DOI: 10.1108/wwop-03-2018-0010
|View full text |Cite
|
Sign up to set email alerts
|

Older people’s experiences of getting help from neighbours

Abstract: Purpose The purpose of this paper is to investigate older people’s views and experiences of getting help from neighbours in order to consider whether such help is situated within neighbourliness and the implications for social care policy which seeks to harness help from neighbours. Design/methodology/approach A qualitative study in which 15 older people from the North of England were interviewed to explore relationships with neighbours, managing day to day life and experiences of getting help from neighbour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 19 publications
2
7
0
3
Order By: Relevance
“…This is in line with earlier studies on strong relations between neighbors that find weak ties to be the starting point for establishing helping arrangements (Henning & Lieberg, 1996;Kohlbacher, Reeger, & Schnell, 2015;Nocon & Pearson, 2000). For those receiving care, this stepwise intensification of neighborhood ties contributes to keeping the relationship with neighbors on an appropriate level for people living next door (Grime, 2018). In our focus group discussions, none of the participants received help beyond small things, such as exchanging keys or help with gardening; intensive support was only reported from the carer's perspective.…”
Section: Discussion: Neighbours As An Alternative To Family Support?supporting
confidence: 88%
“…This is in line with earlier studies on strong relations between neighbors that find weak ties to be the starting point for establishing helping arrangements (Henning & Lieberg, 1996;Kohlbacher, Reeger, & Schnell, 2015;Nocon & Pearson, 2000). For those receiving care, this stepwise intensification of neighborhood ties contributes to keeping the relationship with neighbors on an appropriate level for people living next door (Grime, 2018). In our focus group discussions, none of the participants received help beyond small things, such as exchanging keys or help with gardening; intensive support was only reported from the carer's perspective.…”
Section: Discussion: Neighbours As An Alternative To Family Support?supporting
confidence: 88%
“…This is in line with earlier studies on strong relations between neighbors that find weak ties to be the starting point for establishing helping arrangements (Henning & Lieberg, 1996;Kohlbacher et al, 2015;Nocon & Pearson, 2000). For those receiving care, this stepwise intensification of neighborhood ties contributes to keeping the relationship with neighbors on an appropriate level for people living next door (Grime, 2018). In our focus group discussions, none of the participants received help beyond small things, such as exchanging keys or help with gardening; intensive support was only reported from the carer's perspective.…”
Section: On the Role Of The Neighborhood: The Strengths Of Weak Tiessupporting
confidence: 88%
“…Our results showed a high reciprocity among the participants for neighborhood help as well as helping or receiving help from others; herein people who helped their neighbors also helped others and people who received help from others also obtained help from neighbors. Some researchers have proposed that reciprocity is an important element for a neighborhood-based caring community and the provision of help precedes the receipt of help (Greenfield, 2015 ; Grime, 2018 ). Reciprocity reflects that older adults were not only the recipients but also the providers of assistance for others in the neighborhood and often filled gaps in services and support (Hand et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should investigate the possibilities for neighborhood participation for older adults who do not provide or receive neighborhood help. Grime ( 2018 ) found that older adults were often reluctant to ask for help; therefore, it is important that neighborhood contacts should be promoted by local social institutions and policy makers. Nevertheless, Nocon and Pearson ( 2000 ) warned policy-makers and practitioners against overreliance on the assistance from neighbors, which cannot replace professional social support; accordingly, it is important to combine professional care with (existing) neighborly assistance (Pleschberger and Wosko, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation